A critical review on the solenoid valve reliability, performance and remaining useful life including its industrial applications. (June 2022) - Angadi, Santosh V.; Jackson, Robert L.
Highlights: Reliability and performance of solenoid valve contribute for its safe operation. Remaining useful life prediction of solenoid valve helps to prevent its failure. Performance of coil insulation is critical for functioning of a solenoid valve. Solenoid valves play a key role in hybrid electric vehicles and industry 4.0. Abstract: In this article, the vital operational characteristics such as reliability, performance and remaining useful life (RUL), pertaining to the electromagnetic solenoid valves (SVs), which govern their successful functioning and safe operation during service, are taken into account via a thorough review of the literature. Significance of the coil insulation on the SV reliability and performance is also focused upon. A brief description on the classification of SVs and, more importantly, a summary of the existing research efforts towards automotive and other industrial applications of SVs is included in this review. SVs are also used extensively in the rapidly growing electric and hybrid vehicle industry. The primary aim of this work is to assist the present and future research investigators in realizing the existing research gaps through communicating to them both the past developments and the present status with respect to the above factors associated with the solenoid valve.